Polysaccharide-based nanostructured multilayers with distinct sulfated and aminated composition to improve cells response and biomineralization - Oliveira, Sara M. (2013)
Publicado em "Journal of Tissue Engineering and Regenerative Medicine", vol. 7, supp. 1 (2013)